2019
DOI: 10.21203/rs.2.17386/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Abundance and biogeography of methanogenic and methanotrophic microorganisms across European streams

Abstract: Background: Globally, streams emit significant amounts of methane, a highly potent greenhouse gas. However, little is known about the stream sediment microbial communities that control the net methane balance in these systems, and in particular about their distribution and composition at large spatial scales. This study investigated the diversity and abundance of methanogenic archaea and methane-oxidizing microorganisms across 16 European streams (from northern Spain to northern Sweden and from western Ireland… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 65 publications
(84 reference statements)
1
1
0
Order By: Relevance
“…This is consistent with the previous finding in grassland soils (Kou et al, 2017). However, Sabrekov et al (2019) and Nagler et al (2020) found no good correlation between the activity and abundance of methanotrophs in coniferous forest soils and stream sediments, respectively. Therefore, the efficiency of prediction and modelling of soil methane oxidation potential via methanotrophic abundance may depend on ecosystem types, and it needs further investigation.…”
Section: Biogeographical Distribution Of Methanotrophs In Paddy Soils...supporting
confidence: 91%
“…This is consistent with the previous finding in grassland soils (Kou et al, 2017). However, Sabrekov et al (2019) and Nagler et al (2020) found no good correlation between the activity and abundance of methanotrophs in coniferous forest soils and stream sediments, respectively. Therefore, the efficiency of prediction and modelling of soil methane oxidation potential via methanotrophic abundance may depend on ecosystem types, and it needs further investigation.…”
Section: Biogeographical Distribution Of Methanotrophs In Paddy Soils...supporting
confidence: 91%
“…In fact, a variety of anaerobes (particularly iron and sulfate-reducing bacteria) share a common gene pair (hgcAB) that encodes proteins essential for Hg methylation (Regnell and Watras, 2019;Xu et al, 2021). The diversity of the methanogenic bacterial community in streams is positively linked to water temperature (Nagler et al, 2020), which suggests a lower diversity in boreal lakes and reservoirs, but one that should be quite similar throughout the boreal ecozone. Although mercury bioaccumulation occurs in both reservoirs and natural boreal lakes under the influence of many biotic and abiotic factors (Depew et al, 2013), in reservoirs, this phenomenon is distinguished by a drastic increase in nutrients and in the OM pool available in the water column in, approximately, the first ten years (Lucotte et al, 1999;Schetagne and Verdon, 1999) after their creation due to flooding and erosion.…”
Section: Mehg and Organic Matter A Parallel Fate In Lakes And Reservoirsmentioning
confidence: 99%